Widespread Arterial Thrombosis after ChAdOx1 nCov-19 Vaccination - Giorgio Berlot; Ariella Tomasini; Cristina La Fata; Stefania Pintacuda; Sara Rigutti; Anna Falanga (Case Reports in Critical Care)
Vaccine-induced thrombotic thrombocytopenia is an uncommon complication of COVID-19 vaccines using adenovirus mRNA carriers and has been associated with thrombosis of the cerebral venous sinuses and portal system. We report a case of a 69-year-old woman admitted to the intensive care unit due to stroke caused by thrombosis of the right carotid artery 9 days after receiving the ChAdOx1 nCov-19 vaccine. Further investigations demonstrated multiple thrombi in the arterial tree in the absence of any venous involvement. The clinical course and the treatment are described and discussed.